Maintaining Liquidity to Improve the Performance of Small Businesses - Gumede, Sibusiso Dermot; Takawira, Oliver (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: Aimed at supporting SMME growth, informing policymakers about regulatory improvements, and stimulating economic growth to benefit the population living below the poverty line in South Africa, this research involved participants from SMMEs in the Mangaung region. Design/methodology/approach: An exploratory qualitative study was conducted, utilizing interviews and thematic analysis methods. Findings: The research findings indicated that a majority of participants lacked effective financial management practices, primarily due to an inadequate understanding of the benefits associated with financial management in the context of SMMEs. Research limitations/implications: everal obstacles were identified, including an unstable income cycle influenced by external factors affecting the organization, which leads to substantial deviations from planned financial strategies. Furthermore, time constraints arising from operational demands also hinder the effective management of financial resources. The improper application of financial management principles resulted in a general lack of estimating costs, profits, and financial planning. Practical implications: However, SMMEs that properly implemented these principles experienced prolonged existence due to higher revenue, which has led to growth and sustainability, confirming the benefits of financial management in micro-enterprises. Paper type: Research paper.